A super‐refractory inclusion containing nonstoichiometric spinel from the CO3.0 chondrite Yamato 81020. (3rd May 2021) - Yurimoto, Hisayoshi; Rubin, Alan E.; Itoh, Shoichi; Wasson, John T.
Abstract: We studied a unique super‐refractory inclusion with a core‐mantle structure from CO3.0 Yamato 81020 by secondary ion mass spectrometry, electron microprobe, and scanning electron microscope techniques. The core consists largely of hibonite and nonstoichiometric Al‐rich spinel indicating formation as a liquid at an exceptionally high temperature (>1900 °C). The mantle consists almost entirely of melilite with gehlenitic compositions (ranging from Åk2 to Åk25 ). The oxygen‐ and magnesium‐isotopic compositions of the core and mantle are very different; typically, Δ 17 O (≡δ 17 O − 0.52 δ 18 O) ~–26‰ and ƒMg (mass fractionation of Mg isotopes) ~10‰/amu in the core and Δ 17 O ~–7‰ and ƒMg ~1‰/amu in most of the mantle. The chemical and O, Mg‐isotopic data indicate that the core and mantle formed in separate events, and that the melilite now in the core was formed during the mantle‐melting event, probably filling preexisting voids and surficial cavities. Analyses of core and mantle phases plot along a single 26 Al‐ 26 Mg isochron with initial ( 26 Al/ 27 Al)0 corresponding to 4.8 ± 1.0 (±2σ) × 10 –5, suggesting a similar formation age to normal CAIs in chondrites.